Developing a Systemic Program Evaluation Methodology: A Critical Systems Perspective. (22nd October 2018) - Torres‐Cuello, Maria Alejandra; Pinzón‐Salcedo, Luis; Midgley, Gerald
Abstract : In recent years, there has been an increased interest within the program evaluation field in the introduction of systems thinking concepts. However, most of these introductions have been primarily directed towards supporting the practice of evaluation and not towards making theoretical advancements. This article is focused on introducing systems thinking, and specifically perspectives and concepts from the work in critical systems thinking (CST), at a theoretical level in the program evaluation field, towards a reframing of Fourth Generation Evaluation methodology. The process for carrying out such a reframing is introduced, as well as a description of the major changes produced in the evaluation methodology from incorporating the CST perspective. A new model is proposed, and how this model may be beneficial for conducting an evaluation is discussed. Finally, recommendations are made for future developments. © 2018 John Wiley & Sons, Ltd.